Recycling cementitious constituents of construction demolition waste in asphalt mixes: the case of Lebanon. (2016) - Hassanieh, Dima Z. Al; Chehab, Ghassan R.; Srour, Issam; Kassem, Hussein A.
Stakeholders in the construction industry have lately enacted various initiatives to render it more sustainable. In the case of roadway construction, in particular, tremendous efforts are being placed at various levels to achieve 'green roadways' and 'green asphalt pavements'. Along these lines, this paper discusses the benefits of incorporating recycled concrete aggregates (RCA) from construction demolition waste (CDW) in asphalt mixtures. As such, use of CDW cuts down on the consumption of natural aggregates, a valuable and scarce natural resource in the context of Lebanon - the scope of this study. The study specifically evaluates the feasibility of replacing various percentages of the fine aggregates in hot mix asphalt (HMA) with fine RCA. Asphalt mix designs are developed and evaluated for various percentages of fine RCA, followed with mechanical performance tests. Analysis of testing results for Marshall stability and indirect tensile strength tests confirms the feasibility of replacing up to 30% by mass of fine aggregates in HMA with fine RCA.